1994
DOI: 10.1021/bi00186a013
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Photosystem II Mutants with Perturbed Oxygen-Evolving Properties. 1. Instability or Inefficient Assembly of the Manganese Cluster In vivo

Abstract: Several site-directed photosystem II mutants with substitutions at Asp-170 of the D1 polypeptide were characterized by noninvasive methods in vivo. In several mutants, including some that evolve oxygen, a significant fraction of photosystem II reaction centers are shown to lack photooxidizable Mn ions. In this fraction of reaction centers, either the high-affinity site from which Mn ions rapidly reduce the oxidized secondary electron donor, YZ+, is devoid of Mn ions or the Mn ion(s) bound at this site are unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
321
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(344 citation statements)
references
References 83 publications
21
321
1
1
Order By: Relevance
“…To test the possible role of cyt b 559 under donor-side photoinhibitory conditions, we constructed D170AD1/H22K␣ and D170AD1/Y18S␣ double mutants. D170AD1 mutant cells are able to accumulate stable PSII to the wild-type level but cannot evolve any oxygen (33). Interestingly, our results showed that little PSII was present in D170AD1/ H22K␣ and D170AD1/Y18S␣ double mutants (see Table 1).…”
Section: Continue-wave-epr Spectra Of Wild-type and Mutant Psii Core mentioning
confidence: 54%
“…To test the possible role of cyt b 559 under donor-side photoinhibitory conditions, we constructed D170AD1/H22K␣ and D170AD1/Y18S␣ double mutants. D170AD1 mutant cells are able to accumulate stable PSII to the wild-type level but cannot evolve any oxygen (33). Interestingly, our results showed that little PSII was present in D170AD1/ H22K␣ and D170AD1/Y18S␣ double mutants (see Table 1).…”
Section: Continue-wave-epr Spectra Of Wild-type and Mutant Psii Core mentioning
confidence: 54%
“…Large-scale liquid cultures (3!7 l) were propagated as described previously (Strickler et al 2007). To verify the integrity of the mutant cultures that were harvested for the purification of thylakoid membranes and PSII particles, an aliquot of each culture was set aside and the sequence of the portion of the psbC gene that encodes the large extrinsic loop of CP43 was obtained after PCR amplification of genomic DNA (Chu et al 1994). No trace of the wild-type codon was detected in any of the mutant cultures.…”
Section: Methodsmentioning
confidence: 99%
“…This mutant is weakly photoautotrophic and assembles Mn 4 Ca clusters in ~ 50% of its PSII reaction centers. These assembled Mn 4 Ca clusters function normally [47,52,53] and exhibit normal S 1 and S 2 state multiline EPR signals [50]. In addition, two FTIR studies have shown that the S 2 -minus-S 1 FTIR difference spectrum of D1-Asp170His PSII particles is essentially unchanged from that of wild-type PSII particles [43,46].…”
Section: Aspartate 170 Of the D1 Polypeptidementioning
confidence: 99%